Development of "Eng-Lab" Application Based on Needs Analysis to Improve Professional English in Metro City: English - Rizky Hidayatullah; Umar Alfaruq A. Hasyim; Dimas Dwi Tobing (Journal of English Development, 2024)
The research focuses on the development of "Eng-Lab", an application designed to improve professional English skills in Metro Cities. This research aims to enrich educational technology literature and contribute practical solutions to English language learning challenges. Funded by LITABDIMAS, Director General of Education at the Ministry of Religion, this research identifies English as an important communication tool in the global work environment. The methodology used is a needs-based approach, combining expert insights and participant feedback through interviews and surveys. The result is an innovative, adaptive and interactive learning tool tailored to the user's needs. The app, assessed for its effectiveness, promises to overcome language barriers in the job market and increase economic growth. The study concludes that Eng-Lab, developed through extensive analysis and user feedback, offers a valuable and responsive educational tool for improving professional English proficiency in a diverse and developing economy